The evidence exposure of microplastics in Le Thuy beach of Quang Ngai, Viet Nam - Le Xuan Thanh Thao,; Do Van Manh,; , Huynh Duc Long; Nguyen Thi Linh,; Vo Anh Thu,; Dang Thi Thom,; Nguyen Duy Thanh, (Vietnam Journal of Science and Technology, 2024)
The distribution and characteristics of microplastics in beach and seawater samples at Le Thuy beach, Binh Tri commune, Quang Ngai province were first evaluated in this study. The results showed that the average density of microplastics in beach sand and seawater samples was 1283.33 ± 378.32 pieces/kg and 38.09 ± 10.84 pieces/liter, respectively. Fragments and fibers were the main shape of microplastics with the main polymer composition being PET with proportions of 37.50 and 44.16% in seawater and beach sand samples. The pollution load index (PLI) at level I and the risk assessment based on the chemical composition of the polymer at level II indicates the need to warn to this pollution exposure. This will be the basis for opening new research directions on microplastics in the future.